Pluviosidade, impactos naturais, percepção humana e as inundações em Cáceres/MT : 1971 A 2010 - Santos, Leandro dos (2013)
The concern about the environmental issues has stood out over time and has been featured worldwide. In this context, the impacts on the climate system became inevitable because the degradation of natural resources and successive human interferences on the environment conditioned favorable mechanisms city is the locus of human activities. Among several catastrophic phenomena that often occur, floods stand out because they cause serious damage to individuals, mainly the ones who live in areas susceptible to such occurrences. This research focuses on the analysis of the influence of natural elements, meteorological aspects (rainfall) and anthropogenic variables as potential occurrence of floods in Cáceres-MT from 1971 to 2010, as well as classify the areas with low, medium and high susceptibility; consider the perception of residents who live in the area and in the official records the chronology of those episodes, its impacts and mitigation measures for this problem. Thus, it was adopted as methods of approach/interpretation, a Rhythmic Analysis through the channel of perception Hydrodynamic Impact and Phenomenology which allows to describe the phenomena of experience and to highlight the relationship between man and environment. To systematize the pluviometric rhythm of the region and the major episodes of floods occurred in Cáceres-MT, it was necessary to understand the climate dynamics of the state of Mato Grosso, characterized by the performance of the Continental Equatorial air masses, Continental Tropical and Antarctic Polar. Based on this understanding, the pluviometric data were organized in tables and graphs provided by the weather station of Cáceres-MT, which allowed to characterize the rate of rain in the region in annual, decennial, monthly scale and detail the highest 24 hour rainfall. From these analyzes, it was determined that the region of Cáceres-MT faces strong rainfall variability, where rainy periods contrast with periods of severe drought. The highest rainfall in 24 hours allowed to be determined the major rain events occurred in Cáceres-MT during 39 years of analysis; such rains were confronted with newspaper images, found in the Local Public Records, which helped to define the major episodes of floods occurred from 1971 to 2010. It was used the snowballing technique to collect the data to show the perception of the people who live in the areas considered susceptible to floods in Cáceres-MT. This technique allowed the initial subjects to indicate other participants, and these indicated some others and so on, until the proposed goals were reached. It allowed the use of chains of references, a kind of network among the respondents. At this stage of the research 154 participants were interviewed, of whom 43.5% are male and 56.5 female; with this universe it was discussed issues relating to floods in Cáceres-MT. According to the data, it was noticed that the experiences gained in the region where the subjects live, provide the researcher with great esteem because this way of knowing is part of the supplement of the instrumental data through the subjectivity and allow the systematization of knowledge. It was listed some possible measures for flooding problems in Cáceres-MT, such as the adoption of public policies that guarantee the right of every citizen living in the city, defining the adequate areas of the human buildings and projects that address the physical and hydraulic aspects of the area of study, because it is periodically flooded like the Pantanal Matogrossense. The process of public awareness and education is also necessary since giving the people directions is one of the most effective solutions, because such measures diminish the vulnerability of groups and societies of natural disasters. According to this guideline, it is necessary to develop a Transforming Environmental Education addressing issues related to the environmental development and society, enabling educational activities linked to a set of knowledge, attitudes and environmental sensitivity. Therefore, it is believed that when the human being is aware of the catastrophic events it’s easier to face them.